2017
DOI: 10.1002/2017jc012791
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Freshwater to Spatial Variability of Aragonite Saturation State in the Gulf of Alaska

Abstract: High‐latitude and subpolar regions like the Gulf of Alaska (GOA) are more vulnerable than equatorial regions to rising carbon dioxide (CO2) levels, in part due to local processes that amplify the global signal. Recent field observations have shown that the shelf of the GOA is currently experiencing seasonal corrosive events (carbonate mineral saturation states Ω, Ω < 1), including suppressed Ω in response to ocean acidification as well as local processes like increased low‐alkalinity glacial meltwater discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 66 publications
(146 reference statements)
2
39
0
Order By: Relevance
“…We speculate that our results may be representative of high‐latitude glacial regions outside of the Gulf of Alaska and recommend further sampling of carbon chemistry variables in glacial outflow. The effects suggested here have a significant impact on the regional carbon budget as well as implications for regional fisheries sensitive to ocean acidification (Siedlecki et al, ). This mechanism may therefore be important for projecting coastal ecosystem impacts associated with the continued oceanic uptake of atmospheric CO 2 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We speculate that our results may be representative of high‐latitude glacial regions outside of the Gulf of Alaska and recommend further sampling of carbon chemistry variables in glacial outflow. The effects suggested here have a significant impact on the regional carbon budget as well as implications for regional fisheries sensitive to ocean acidification (Siedlecki et al, ). This mechanism may therefore be important for projecting coastal ecosystem impacts associated with the continued oceanic uptake of atmospheric CO 2 .…”
Section: Discussionmentioning
confidence: 87%
“…The larger Northeast Pacific Model (NEP) (Curchitser et al, 2005) supplies the boundary conditions and the initial conditions of all model state variables except dissolved inorganic carbon (DIC) and TA. Inclusion of DIC and TA is based on previous implementations within the ROMS framework (Fennel et al, 2008), with modifications for ammonium cycling impacts on the carbon cycle and freshwater influence (Siedlecki et al, 2017).…”
Section: Model Descriptionmentioning
confidence: 99%
“…As this region continuous to rapidly deglaciate (Arendt et al, 2002;Larsen et al, 2007;O'Neel et al, 2005), not only the amount of freshwater discharge will increase (Beamer et al, 2017), but most of the glaciers surrounding the GOA will recede away 15 from the ocean and into higher elevations (Huss and Hock, 2015), resulting in a change of the biogeochemical composition of freshwater. This and previous studies have shown that freshwater discharge is the largest driver of the nearshore inorganic carbon dynamics in summer and fall, and is known to exacerbate the effects of ocean acidification Siedlecki et al, 2017;Pilcher et al, 2018). Understanding the composition of freshwater sources is, therefore, particularly important for the study of long-term trends of ocean acidification in the GOA-LME.…”
Section: Discussionmentioning
confidence: 59%
“…Overall, freshwater fluxes used in this study are more realistic than in previous studies because they are derived from a temporally and spatially highly resolved hindcast simulation forced with meteorological reanalysis data 5 sets. Compared to previous studies (Royer, 1982;Wang et al, 2004;Hill et al, 2015;Siedlecki et al, 2017), this current model configuration is better able to reproduce low salinity levels in coastal areas across the GOA and can thereby more adequately reproduce the Alaska Coastal Current (Danielson et al, in review).…”
Section: Physicsmentioning
confidence: 88%
See 1 more Smart Citation